Erythropoietin therapy in a case of neonatal anemia after exposure to natalizumab throughout pregnancy - Elisabetta Godano; Fabio Barra; Alessandra Allodi; Antonella Ferraiolo; Alice Laroni; Giovanni Novi; Giovanni Luigi Mancardi; Claudio Gustavino; Cesare Arioni (BMC, 2021)
Abstract Background Natalizumab is a monoclonal antibody approved for the treatment of patients with relapsing-remitting multiple sclerosis. According to the current clinical recommendations, its use during pregnancy should be carefully evaluated only in women with highly active disease who plan a pregnancy or have an unplanned pregnancy, after accurate counseling about eventual maternal disease relapse due to therapy suspension. Case presentation This brief case report describes a case of documented anemia that we observed in a newborn whose mother with relapsing-remitting multiple sclerosis was treated with an extended dosing protocol of natalizumab throughout pregnancy. The newborn received the infusion of erythropoietin every seven days from the fortieth day of life; subsequently, the status of anemia underwent clinical resolution. Conclusions This case report confirmed that natalizumab can cause disorders of hematopoiesis, including anemia, thrombocytopenia, or pancytopenia, in newborns of patients treated during pregnancy. A multidisciplinary team, including experienced pediatricians and pediatric hematologists, has a critical role in managing newborns delivered by women, being treated with natalizumab for treating relapsing-remitting multiple sclerosis during pregnancy.